The “halal” criterion in the reformist conception of conventional finances - Edaich, Said (The Opole Studies in Administration and Law, 2020)
In this paper, the author presents “halal finance” as a reform of the conventional financial system. Starting with a presentation of the vision of the meaning of the reform, which differs from that perceived by old civilizations, he tries to cast light on the role of the reform and its impact on the development of society in general. At the second stage, attention is paid to the connotation of the new management of public affairs and financial reforms. In the last part, the author demonstrates how conventional finances integrate halal finance as a reform considering the changes that have marked the financial industry in recent years, especially the explosion of petrodollars, the deregulation and liberalization of financial markets.